PENGARUH PENGGUNAAN APLIKASI ANDROID CERITA ANAK BERBASIS PENGUATAN PENDIDIKAN KARAKTER TERHADAP HASIL BELAJAR SISWA KELAS 4 DI SD MUHAMMADIYAH 8 DAU - Arinta Rezty Wijayaningputri; Innany Mukhlishina; Murtyas Galuh Danawati (Universitas Muhammadiyah Surabaya, 2022)
In the 21st century, the development of smartphone media is a tool for students to learn online. During the Covid-19 pandemic, SD Muhammadiyah 8 Dau found it difficult to do online learning. SD Muhammadiyah 8 Dau has used media with various learning methods for offline learning, but online learning media is still very limited. The results of the interviews also showed that in class IV there was no media for learning children's stories that were in accordance with the applicable curriculum. In addition, whether the learning media for children's stories based on strengthening character education has been effective and influential. In accordance with the government's recommendation, namely the cultivation of character education in elementary schools. The purpose of this study was to measure the effect of using android applications as a learning device based on strengthening character education on student learning outcomes. The design of this research is pretest-posttest-group design, with a simple random sampling method that is determined based on the results of the pretest. The results of the study were strengthened by the results of the analysis through the SPSS program which showed the results of the average pretest score of 79.38 and the posttest average value of 84.38. In addition, the T-test results in the Sig.(2-Tailed) table have a value of 0.150 where the value is > 0.05. So it can be stated that there is an effect of using the android application for children's stories on the learning outcomes of fourth grade students at SD Muhammadiyah 8 Dau.Â Keywords: Android Applications, Children's Stories, Strengthening Character Education, Learning Outcomes